Climate change effects and livelihood-adaptation strategies by the urban poor in Ibadan, Nigeria - Ola, Akeem (Town and Regional Planning, 2022)
As with many developing countries, one of Nigeria’s major challenges to socio-economic development is climate change. This article examines the effects of climate change on the livelihood activities of the urban poor in Ibadan, Nigeria. Adopting a cross-sectional survey design, the research relied essentially on primary data. A structured questionnaire was used to obtain primary data from 481 purposively selected urban residents engaging in different livelihood activities. Data collected were analysed using descriptive and inferential statistical techniques. The Respondents’ Agreement Index was used to measure the respondents’ awareness of climate change and climate change adaptation strategies. Tobit Regression Model was used to analyse the factors influencing climate change adaptation strategies, while the effects of climate change on residents’ livelihood were measured using Multinomial Logistic Regression. Findings revealed that respondents were involved in diverse livelihood activities, ranging from trading to civil service. Long dry seasons, excessive heat, irregular rainfall patterns, and frequent floods make respondents aware of climate change. Low patronage by buyers, low productivity, and reduction in income were the major effects of climate change on livelihood activities. Diversifying income sources was the main adaptation strategy. Strengthening the physical planning system to build the city’s resilience and adaptive capacity to climate-related disasters was recommended.